Genetic variants of U. parvum and their role in the development of inflammatory diseases of the urogenital system - M. R. Rakhmatullina; K. I. Plakhova; O. N. Igonina (State Scientific Center of Dermatovenereology and Cosmetology, 2017)
The article discusses the results of a study aimed at determining the frequency of different genetic variants of U. parvum in women with inflammatory diseases of the urogenital system and clinically healthy subjects. Molecular typing of 40 samples of U. parvum taken from women with different forms of inflammatory diseases of the urogenital system was performed for the mba gene. The authors revealed a relationship between clinical manifestations of inflammatory diseases of the urogenital system caused by U. parvum and different U. parvum serovars. An infection with 6 U. parvum serovar results in the development of inflammatory processes in the form of cervicitis or vaginitis accompanied by subjective manifestations more frequently than an infection with other serovars under examination (1 and 3) (p < 0.05).